How does the new energy demonstration city pilot policy affect energy-intensive enterprises’ ESG? A quasi-natural experiment from China - Huan Zheng; Jinqiu Yang; Shengyu Xu (Sustainable Futures)
The new energy demonstration city (NEDC) pilot policy is an important attempt of the government to promote the energy system transition and further advance China's sustainable society development. The main focus of the NEDC is energy-intensive enterprises, however, the policy effect on these enterprises’ environmental, social, and governance (ESG) is still underdiscussed. This study uses a panel data of Chinese listed energy-intensive enterprises during 2009–2022 and a difference-in-differences model to examine whether the NEDC boosts corporate ESG. The findings indicate that the NEDC can effectively improve the ESG of energy-intensive enterprises, and this result remains robust following various tests. We also decompose ESG into three sub-factors, i.e., environmental (E), social (S) and governance (G), revealing the NEDC's promotional influence on S and G. Our quantile analysis shows a more significant enhancing effect of the NEDC on enterprises with lower ESG than on those with higher ESG. The mechanism analysis reveals that the NEDC affects enterprises’ ESG through technological innovation, confirming the Porter hypothesis in China. Finally, our research confirms that the promotional effect of the NEDC on enterprises’ ESG is notably reflected for non-state-owned enterprises and enterprises in the eastern area. These findings suggest that the Chinese government should adhere to implementing the NEDC in the long term, promote technological innovation, and adjust this policy appropriately, so as to make the policy effect longer and broader, and finally achieve sustainable development goals.